0009 Restless Leg Syndrome: Does It Start With A Gut Feeling?. (12th April 2019) - Blum, Daniel J; During, Emmanuel; Barwick, Fiona; Davidenko, Polina; Zeitzer, Jamie M
Abstract: Introduction: Emerging research links gut microbial health with sleep. One common sleep disorder in which the microbiome may play a role is restless legs syndrome (RLS). While the pathogenesis of RLS is not fully understood, a relative state of brain iron deficiency has been described in patients with RLS and appears to induce changes in several pathways (adenosinergic, glutamatergic and dopaminergic) known to be involved in the disease. Insufficient iron may be secondary to dietary iron deficiency or, potentially, gut inflammation. We hypothesized that small intestinal bacterial overgrowth (SIBO), a condition associated with gut dysbiosis (i.e., normally rare gut-residing bacteria are over-represented in the gut), is associated with RLS and may moderate the observed inter-patient variability in serum iron availability. Methods: Participants are being recruited at the Stanford Sleep Center for three groups: RLS and low peripheral iron stores (<50ng/mL and/or transferrin saturation <18%), RLS and normal peripheral iron stores, and insomnia (control). Participants complete questionnaires concerning sleep and SIBO symptoms and are sent home with a fecal collection kit (Fecal Swab Collection and Preservation System, Norgen Biotek) and a SIBO kit (SIBO Home Breath Test Kit, Quintron). Fecal samples are assayed by the University of Minnesota Genomics Center with microbial community profiling evaluated by 16S ribosomal RNA (16S rRNA) gene sequencing protocols. SIBO breath samples are evaluated by Aerodiagnostics for hydrogen and methane abnormalities. Results: Seven participants diagnosed with RLS (3 men, 4 women) have thus far completed the protocol. All indicated poor sleep quality (PSQI ≥ 5) and moderate to severe symptoms of RLS (IRLS scores ranging from 13 to 34/40). SIBO was present in all 7 participants (100%) whereas general population rates are estimated to be 6-15%. Conclusion: These preliminary data suggest that SIBO may be more prevalent among patients with RLS. Additional analyses will examine fecal microbial composition, subtypes of RLS iron deficiency, and comparisons with insomnia. Support (If Any): Pau Innovation Gift Fund Seed Grant